CLINICAL SCORE (APACHE II, SAPS II) AND IPORP IN PREDICTING COMPLICATED PERITONITIS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
Based on the results obtained, it is advisable to recommend that all patients with widespread peritonitis undergo express immunological examination already on the first day after surgery. The use of this method in combination with traditional clinical scales (APACHE II, SAPS II) increases the accuracy of risk stratification, allows timely identification of patients with an unfavorable prognosis and provides the possibility of more targeted preventive and therapeutic measures.